Studies on the promoting effect of sulfate species in catalytic dehydrogenation of propane over Fe2O3/Al2O3 catalysts. Issue 2 (21st November 2014) - Sun, Yanan; Wu, Yimin; Shan, Honghong; Wang, Guowei; Li, Chunyi
Abstract : The nature of the effect of sulfate species on properties and dehydrogenation performance of Fe2 O3 /Al2 O3 catalysts was systematically studied. Abstract : The promoting effect of sulfate species in propane dehydrogenation over Fe2 O3 /γ-Al2 O3 catalysts is systematically elucidated by using iron(iii ) or iron(ii ) sulfate as the precursor, pre-treating with SO2 or introducing SO2 with propane as the reactant. At 560 °C, up to 23 wt% propylene yield with 80% selectivity is obtained. It is demonstrated that the introduced sulfate species exist in the form of SO4 2− and strongly interact with the support and Fe via the Al–O–S bond and the Fe–O–S bond. On one hand, it suppresses the formation of Fe x C species and thus the cracking reaction. On the other hand, it leads to an enhanced adsorption capacity of propane. Meanwhile, the initial C–H bond activation and subsequent rupture with the formation of Fe–C3 H7 and OH are facilitated, resulting in excellent dehydrogenation performance. Online MS, XPS, XRD and reaction–regeneration–sulfuration results show that the loss of sulfate species by the reduction to S 2− and release in the form of SO2 is the main reason for the deactivation of the sulfated catalysts.